Representative Of Hedonism Ideology In A Novel Of The Great Gatsby By F. Scott Fitzgerald - Sujarwo; Ananda Astrini Muhammad; Sitti Sahraeny; M. Amir P; Herawaty Abbas; Hasnani (CV. Eureka Murakabi Abadi, 2022)
This study analyzes the novel that entitled The Great Gatsby, written by F. Scott Fitzgerald. Based on the novel, the character tries to do anything to get their happiness such as wasting their money for unimportant things which is called hedonism. This study aimed to analyze the representative of hedonism ideology and the culture in New York in 1920s in the Great Gatsby novel written by F. Scott Fitzgerald. The theories that are used in this study are hedonism theory. This study uses sociological approach and library research which takes some information related to the research problems from books and other literatures to gather the data. The result of the analysis to answer the first research problem shows that from seven kinds of hedonism, there are two kinds that are found by researchers in this study; Hedonistic Egoism, and Hedonistic Utilitarianism. The first kind is Hedonistic Egoism that can be seen when Tom and Daisy move to another city and let Gatsby clean up the mess that they have made. The last kind is Hedonistic Utilitarianism that can be seen when Gatsby often holds parties for anyone.